Haptic Feedback for Microrobotics Applications: A Review - Pacchierotti, Claudio; Scheggi, Stefano; Prattichizzo, Domenico; Misra, Sarthak (Frontiers in Robotics and AI, 2016)
Microrobotics systems are showing promising results in several applications and scenarios, such as targeted drug delivery and screening, biopsy, environmental control, surgery, and assembly. While most of the systems presented in the literature consider autonomous techniques, there is a growing interest in human-in-the-loop approaches. For reasons of responsibility, safety, and public acceptance, it is in fact beneficial to provide a human with intuitive and effective means for directly controlling these microrobotic systems. In this respect, haptic feedback is widely believed to be a valuable tool in human-in-the-loop teleoperation systems. This article presents a review of the literature on haptic feedback systems for microrobotics, categorizing it according to the type of haptic technology employed. In particular, we considered both tethered and untethered systems, including applications of micropositioning, microassembly, minimally invasive surgery, delivery of objects, micromanipulation, and injection of cells. One of the main challenges for an effective implementation is stability control. In fact, the high scaling factors introduced to match variables in the macro and the micro worlds may introduce instabilities. Another challenge lies in the measurement of position and force signals in the remote environment. The integration of microsized sensors may significantly increase the complexity and cost of tools fabrication. To overcome the lack of force-sensing, vision seems a promising solution. Finally, although the literature on haptic feedback for untethered microrobotics is still quite small, we foreseen a great development of this field of research, thanks to its flexible applications in biomedical engineering scenarios.